2009
DOI: 10.1055/s-0029-1215333
|View full text |Cite
|
Sign up to set email alerts
|

Pico-Salax versus polyethylene glycol for bowel cleanout before colonoscopy in children: a randomized controlled trial

Abstract: Children tolerate Pico-Salax better than PEG-ELS for bowel cleanout before colonoscopy. This study did not demonstrate superiority of effectiveness or safety for either regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 25 publications
6
54
0
1
Order By: Relevance
“…There may be a risk if only one of these perspective is used when bowel cleansing before colonoscopy is planned. Bowel cleansing with PEG was experienced as the most difficult part of the procedure by both children and parents and this result is in accordance with previous quantitative studies [20,21,22,23]. These quantitative studies show difficulties with PEG intake based on a large volume and bad taste, however this study also shows that children were not psychologically prepared for this procedure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There may be a risk if only one of these perspective is used when bowel cleansing before colonoscopy is planned. Bowel cleansing with PEG was experienced as the most difficult part of the procedure by both children and parents and this result is in accordance with previous quantitative studies [20,21,22,23]. These quantitative studies show difficulties with PEG intake based on a large volume and bad taste, however this study also shows that children were not psychologically prepared for this procedure.…”
Section: Discussionsupporting
confidence: 90%
“…The recommended intake of PEG is 25-35 ml/kg bodyweight per hour until clear intestinal fluid is obtained, either orally or by nasogastric tube [19]. Previous quantitative studies show that the intake of large volumes of bad-tasting laxative was the most difficult part of the procedure prior to colonoscopy from both the child's and parents' perspective [10,20,21,22,23]. A limitation of research in this area is that children's and parents' experiences of bowel cleansing have been largely neglected [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy rate of high-volume regimens was assumed to be 80%. 11 In addition, a difference of $20% of efficacy (ie, rate of successful bowel cleansing) between the high-volume and each of the low-volume regimens was assumed to be clinically relevant. To maintain the hypothesis, 5% type I error (a), and 80% power (= 1 -b), the required sample size was estimated to be 70 patients per each arm.…”
Section: Discussionmentioning
confidence: 99%
“…Single published randomized trials with pediatric populations demonstrated high efficiency of both PEG with electrolyte solutions and oral NaP [131][132][133] . However, oral administration of NaP to children has limitations because of serious adverse effects, such as electrolyte and fluid disturbances and acute kidney injury [133] .…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…One RCT showed good bowel cleaning with sennosides, whereas bisacodyl with an enema-based protocol had a high rate of poor preparation (37%), resulting in the need for repeated examinations [141] . Other alternative bowel preparation regimens are based on osmotic agents alone or combined with laxatives [21,131,132,[141][142][143][144][145][146][147][148] . Although excellent or good bowel cleansing rates were reported in 40%-100% of the children, depending on the regimen, these studies are mostly non-randomized, with a limited number of patients.…”
Section: Pediatric Patientsmentioning
confidence: 99%